Nutrients Uptake and Cycling of Pineapple Planted on Tropical Peat - Ahmed, Osumanu Haruna (1999)
The obectives of the study were: (i) To quantify the dry matter production and nutrients uptake under burnt and unburnt pineapple residue management practices, (ii) To determine the nutrients capacity and intensity of tropical peat under pineapple cultivation, (iii) To quantify the movement of nutrients in pineapple production system, and (iv) To conduct economic valuation of the burnt and unburnt pineapple residue management practices. Treatments used were: (i) Leaves residue removed and no fertilization, (ii) Leaves residue burnt and no fertilization, (iii) Leaves residue removed and fertilization, and (iv) Leaves residue burnt and fertilization. The experimental unit was individual plant planted in 4 m x 12 m plot. Altogether 300 pineapple plants were planted in this plot having a randomized complete block design (RCBD) with 4 replications. Phosphorus and K were applied in the fonns of China phosphate rock and muriate of potash at the rates of35.56 P and 556.56 K kglha. At maturity, 3 plants were sampled from each treatment and partitioned into roots, stem, leaves, fruit, crown and peduncle and their dry weight, P, K, Ca and Mg concentrations determined. Soil sampling at the depths of 0-5, 5-25 and > 25 cm was done before, during and after fertilization stages. Soil solution P, Ie, Ca and Mg